Responsivitas Negara Terhadap Fenomena Perkembangan Mural Di Kota Denpasar - Setyadarma, I Putu Bayu; Erawan, I Ketut Putra; Jayanthi Mertha, A.A. Sagung Mirah Mahaswari (Jurnal Nawala Politika, 2019)
ABSTRACT The purpose of this research was to Discover the respond of Denpasar City Government about the development of Denpasar mural. Political communication theory and political show theory been used as a research theory and became a thinking framework of this research. Qualitative descriptive was the method of the research. This research discovered that Mural in Denpasar City fulfilling aspects of the approach of political communication through several aspects such as political communicator, political message, political media communication, political target, and the effect of political communication. Denpasar city government and the artist had a different role in the existence of Mural in Denpasar. In certain condition, both sides need each other. Mural artists had experience in the making of image scenario of Mural, while Denpasar city government have authority in giving permission of location and theme whose be appointed by Mural community. Keywords: State Responsiveness, Mural, Artists, Denpasar City Government